Point of Care Tests VerifyNow P2Y12 and INNOVANCE PFA P2Y Compared to Light Transmittance Aggregometry After Fibrinolysis. (October 2018) - Roule, Vincent; Ardouin, Pierre; Repessé, Yohan; Le Querrec, Agnès; Blanchart, Katrien; Lemaitre, Adrien; Sabatier, Rémi; Borel-Derlon, Annie; Beygui, Farzin
Detection of high on-treatment platelet reactivity (HPR) by point-of-care tests has not been validated after successful fibrinolysis for ST-elevation myocardial infarction. We assessed the validity of the point-of-care VerifyNow P2Y12 (VN) and INNOVANCE PFA P2Y (PFA) tests on HPR compared to light transmittance aggregometry (LTA) in these patients. The HPR was identified in 10 (34.5%) patients, 15 (51.7%) patients, and 14 (50%) patients using LTA, VN, and PFA, respectively. Discrepancies were observed between the tests despite significant correlations between platelet reactivity measures by LTA and VN ( r = 0.74; P < .0001) and LTA and PFA ( r = .75; P < .0001). Compared to LTA, VN and PFA were associated with a 92% and 53% and 92% and 64% positive predictive value (PPV) and negative predictive value (NPV), respectively, in detecting HPR. When combined, VN and PFA results yielded 90% and 100% PPV and NPV values if discrepancies between the 2 tests were considered as non-HPR. The VN or PFA identify patients without HPR correctly but overestimate the proportion of HPR patients. The association of the 2 tests, in case of HPR, improves the accuracy of the detection of HPR.